A County-Based Northern Bobwhite Habitat Prioritization Model for Kentucky - John J. Morgan; Gary Sprandel; Ben A. Robinson; Keith Wethington (National Quail Symposium Proceedings, 2017)
Planning the management of northern bobwhite (Colinus virginianus) habitat at a statewide-scale is daunting. Native grassland restoration is difficult to manage in Kentucky because . 99% of the Commonwealth’s original grassland area has been lost to agriculture, succession, and development. We created a county prioritization model designed to target areas of grasslands and landowners likely to participate in conservation programs. Our goal was to identify 10% of the state as high priority for bobwhite habitat restoration. We created an east and west model divided by the Appalachian Mountains. The west model was designed to target production-oriented operators farming marginal lands, whereas the east model targeted reclaimed minelands. We used agricultural, landcover, and staff data to build county prioritization models in 2006 and 2011. The models targeted 16.6% and 17.6% of the state in 2006 and 2011, respectively. However, if areas of large, contiguous blocks of forests were excluded, the area total was much closer to 10%. Fifty percent of the high priority counties changed in the west model, and 33% of the counties in the east model changed over 5 years. Implementing a county prioritization model in conjunction with a finer-scale, biological targeted approach could focus conservation efforts with greater potential for success, but the models should be reconstructed at 5- to 10-year intervals to account for changes in conservation delivery potential. A modification of our technique may serve to validate or as an alternative to improve National Bobwhite Conservation Initiative 2.0.
Keywords: Colinus virginianus; delivery; grasslands; habitat; Kentucky; model; northern bobwhite; prioritization; restoration; target